Strengthening National Resilience through the Implementation of Organizational Citizenship Behavior (OCB) in Higher Education - Wiwik Handayani; Haryo Sulistyantoro; Rizky Darmawan; Erna Tri Rusmala Ratnawati (Future Science, 2022)
Globalization will present opportunities and challenges to watch out for, especially for Indonesia as a country rich in natural resources, human resources, and culture. There are various challenges in the era of globalization, including national defense and security, as well as a weak sense of national identity that makes them vulnerable to division. Currently, the Indonesian people face various challenges in implementing and implementing Pancasila values. At the same time, Pancasila is the fundamental value and ideology in the life of the nation and state for the people of Indonesia. Awareness of national security is a willingness to serve the country and sacrifice to defend the country. National security is closely related to ensuring the existence of the Unitary State of the Republic of Indonesia and realizing the nation's ideals. This study aims to strengthen national resilience by applying Organizational Citizenship Behavior (OCB) in Higher Education. This research is a literature review research using books and articles that focus on national resilience and Organizational Citizenship Behavior (OCB). The results of the study show that education and strengthening of national resilience are carried out both mandatory and voluntary. Volunteering in understanding the OCB concept encourages everyone to produce the best performance without coercion. Improving knowledge and skills voluntarily in teaching and educating students will significantly increase learning motivation. Learning motivation tends to be more easily formed voluntarily if the teachers also have the same attitude. Volunteering included in the teaching and learning process or education in higher education will strengthen the process of disseminating the ideology of national resilience, which will also result in voluntary national resilience behavior.